Penerapan Pembelajaran Yang Dari Pemberian Soal Cerita Pada Siswa Kelas I SLTPN Kecamatan Banuhampu Sungai Puar - Heleni, Susda (Jurnal Pilar Sains, 2003)
Developing students skill in solving story-based question is one of infortant objectives mathematics teaching atschool, since such story-based question will upgrade student’s ability in problem solving. Problem solvingability should be possed by students, because through this activity student are expected to understandmathematic materials well, and indirectly the creativity of students can be attracted. In fact, during learningprocess is undergoing, most students find it difficult answering story-based question. On other hand, if thequestion not based on stories, they can answer perfectly. Besides that teachers conjess that they rarely give andteach story-based question for such questionsplaced at last number and teacher are unexperienced on how tosolve the questions. Therefore, class action research is badly needed to increase student learning result basesdon story-based question learning. By doing so, giving story-based question refering to the daily students willgive much attention the use and benefit of mathematics. It stand to reson students will give much attentiontoward the leaning process that will give positive effect toward their learning outcome. The result in thisresearch is learning with started with giving the essay that can increase the studying result of the 1st classstudent in SLTPN at the subdistrict Banuhampu Sungai Puar in Period 2000/2001